CAR Based Immunotherapy of Solid Tumours—A Clinically Based Review of Target Antigens - John Maher; David M. Davies (Biology, 2023)
Immunotherapy with CAR-engineered immune cells has transformed the management of selected haematological cancers. However, solid tumours have proven much more difficult to control using this emerging therapeutic modality. In this review, we survey the clinical impact of solid tumour CAR-based immunotherapy, focusing on specific targets across a range of disease indications Among the many candidates which have been the subject of non-clinical CAR T-cell research, clinical data are available for studies involving 30 of these targets. Here, we map out this clinical experience, highlighting challenges such as immunogenicity and on-target off-tumour toxicity, an issue that has been both unexpected and devastating in some cases. We also summarise how regional delivery and repeated dosing have been used in an effort to enhance impact and safety. Finally, we consider how emerging armouring systems and multi-targeted CAR approaches might be used to enhance tumour access and better enable discrimination between healthy and transformed cell types.